Experience and Perspectives of Teaching Bioethics While Training Pediatricians and Family Physicians - N.V. Nagornaya; A.V. Dubovaya; Ye.V. Bordyugova; Ye.V. Pshenichnaya (Zaslavsky O.Yu., 2013)
During the process of professional development of pediatricians and family physicians, along with the improvement of knowledge and skills, constant improvement of ethical literacy, formation of humane treatment of the child and his family must take place. «Tests on Bioethics and Medical Ethics for Pediatricians» developed by the staff of the department of pediatrics of faculty of internship and postgraduate education of Donetsk national medical university named after M. Gorky and used within 7 years in postgraduate education help the doctor to choose the right tactics to communicate with patient and family, colleagues, contribute to the formation of ethical thinking, which indicates the feasibility of their use in pedagogical process.